Multiple perspectives on the teaching and learning of mathematics in rural South African schools in the context of national curriculum reform - Morar, Tulsidas (Curtin University, 2003)
This study investigates the teaching and learning of mathematics in four rural schools in the Eastern Cape Province of South Africa. The study is set against the backdrop of Curriculum 2005 (C2005) - an outcome based curriculum reform initiative that has been introduced to all South African schools. The objective of the study is to investigate the teaching and learning practices of four rural teachers of mathematics in this complex reform milieu. The following broad research question guides this study: "How do teachers interpret and implement the new mathematics curriculum in terms of a political perspective (how teachers and learners are connected to the curriculum); a socio cultural perspective (what adjustments the teacher makes to accommodate the learners' circumstances); and a practical perspective (how the teacher implements the goals of C2001?" The South African situation provides a unique and particularly challenging context for teaching and learning and curriculum reform. It is understood that schools differ - and therefore curriculum issues cannot be solved through general pronouncements but rather viewed from a multiplicity of perspectives. In this thesis, I examine the teaching and learning of mathematics in four rural classrooms in the Eastern Cape. By way of honouring the contextual complexity of the situation, 1 have adopted a multiple perspectives approach to analysing what goes on in these four classrooms. I use a political perspective to help understand how power operates in the curriculum process.I employ a socio cultural perspective to examine how the curriculum process attends to the local circumstances of teachers and learners. A practical perspective is used to examine how the curriculum is implemented in a technical sense. This constructivist interpretive study employs the techniques of case study and narrative inquiry to study the curriculum practices of four teachers. Multiple methods - including interviews, participant observation and video recording - were used to gather data. Narrative accounts of the teaching and learning of mathematics were constructed and then analysed using the three perspectives. The study concludes that the curriculum can be interpreted at different levels formal, perceived, operational and experiential - and each level can be analysed in terms of the political, socio cultural and practical. Bringing these three perspectives together is a challenging, but necessary task in order to understand and act upon the complexities of educational reform in rural South African classrooms.